Lonely: A Response on Alan Walkers Faded by Gamel Awan - - Thohiriyah (Universitas Muhammadiyah Semarang, 2017)
n this paper, the writer tries to analyze a creative response done by Gamel Awan over Alan Walkers Fadedentitled Sepine/Lonely. The purpose of this writing is to investigate how nature is seen and treated by humans. This research uses ecocriticism as the theory and methodology. In responding Alan Walkers song, Gamel Awan recomposed the lyric as well as the music by employing the Javanese language and music arrangement. By defining Faded as lonely, the text poses at least two hypothetical propositionsover nature representationas follows: 1) nature is emplaced as an isolated space; and 2) nature is only functioned as a spoil tip.